Three-dimensional (3D) palladium-zinc oxide nanowire nanofiber as photo-catalyst for water treatment. (15th September 2016) - Choi, Jungsu; Chan, Sophia; Joo, Hyunjong; Yang, Heejae; Ko, Frank K.
Abstract: Zinc Oxide Nano Wires (ZNWs) has been considered as a promising material for purification and disinfection of water and remediation of hazardous waste owing to its high activity and lower cost. In this study, three-dimensional (3D) structured palladium (Pd)/ZNWs were synthesized on the fabricated electrospun nanofibers and explored for enhancement of organic matter (OM) removal efficiency in water by suppressing electron–hole recombination during photocatalytic activity and increased surface area. The densely populated ZNWs were fabricated on the electrospun nanofiber by electroless plating (EP) and hydrothermal synthesis. In order to improve photocatalytic efficiency, a thin layer of Pd was coated prior to ZNWs growth to induce suppression of electron hole recombination produced during catalyst activity. The creation of a highly porous network of nanofibers decorated with ZNWs resulted in an increase of specific removal rate (SRR) of OM from 0.0249 to 0.0377 mg CODCr removed/mg ZNWs-hr when ZNW were grown on a Pd layer. It is believed that the demonstration of OM removal in the water through Pd/ZNWs membrane and enhanced photocatalytic activity under UV irradiation from layered structure can broaden potential applicability of Pd/ZNWs membranes for various photo catalytic water treatment. Graphical abstract: Highlights: 3D structured ZNWs were uniformly grown on the palladium coated nanofibers. Enhancement of OM removal through suppressing electron hole recombination. Removal of OM was found to be 96.6% from the Pd/ZNWs nanofiber. Pd/ZNWs membrane provide a powerful photocatalyst process for water treatment.